Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Struktur Modal, Pertumbuhan Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Di Indonesia Tahun 2015-2018 - Nursanita Nasution; Faris Faruqi; Sri Rahayu (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
This study aims to examine the effect of ownership managerial, institutional ownership, capital structure, growth company and profitability on the value of the company in the company manufacturers listed on the Indonesia Stock Exchange (IDX). This research using 27 manufacturing companies listed on the Stock ExchangeIndonesia selected by using purposive sampling method during 2015 to 2018. This type of research is quantitative causality, which is analyzed using multiple linear regression analysis method of panel data with the help of tools Eviews 11 to process the data. The results of the study show that profitability has a significant positive effect on the value of company, the greater the profit obtained, the greater as well as the company's ability to pay dividends. That matter can give a positive signal to investors so that the stock will more desirable which will then increase the value of the company the.